Molecular phylogenetic assessment of the genus Scutellinia (Pezizales: Pyronemataceae). (2nd January 2023) - Angelini, Paola; Bistocchi, Giancarlo; Arcangeli, Andrea; Venanzoni, Roberto; Rubini, Andrea
Abstract: The genus Scutellinia consists of cup fungi belonging to the Pyronemataceae (Ascomycota). It comprises more than 100 species with a worldwide distribution. Species delimitation is based on morphological characteristics of the ascocarps, such as spore size, form and ornamentation as well as size and morphology of hairs that typically cover the external surface of the ascoma. These characters are, however, highly variable and species recognition challenging. In this paper, ribosomal DNA traits such as the internal transcribed spacer and the large subunit ribosomal gene were sequenced in several Scutellinia samples and, along with all available sequences on public database, used to improve the knowledge about taxonomy and phylogeny of this genus. Based on sequence similarity and trees topology, about 50 phylogenetic species were recognized and their phylogenetic relationships disclosed.